2018
DOI: 10.2337/dc17-1763
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Costs Associated With Incident Complications in Patients With Type 2 Diabetes in Germany

Abstract: Type 2 diabetes complications have a significant impact on total health care costs in the SHI system, not only in the quarter of event but also in subsequent years. Men and women from different age-groups differ in their costs for complications. Our comprehensive estimates may support the parametrization of diabetes models and help clinicians and policy makers to quantify the economic burden of diabetes complications in the context of new prevention and treatment programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
3
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 29 publications
8
99
3
3
Order By: Relevance
“…Given that T2DM is a disorder with a metabolically complex nature, it can be suggested that the pathogenesis of diabetes-related CI is multifactorial. 1 However, to date, no study has been conducted particularly to assess the cognitive function of people with T2DM to produce a profound and comprehensive clinical characterization in order to make it possible to examine the effect of numerous cognitive risk factors. Even though macrovascular disease and hypertension per se are considered as major possible risk factors, the odds are that genetic susceptibility plays an important role as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that T2DM is a disorder with a metabolically complex nature, it can be suggested that the pathogenesis of diabetes-related CI is multifactorial. 1 However, to date, no study has been conducted particularly to assess the cognitive function of people with T2DM to produce a profound and comprehensive clinical characterization in order to make it possible to examine the effect of numerous cognitive risk factors. Even though macrovascular disease and hypertension per se are considered as major possible risk factors, the odds are that genetic susceptibility plays an important role as well.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is considered to be a costly disease worldwide due to its many complications. 1,2 The chronic nature of the disease and its associated complications impose heavy economic burdens and reduce the quality of life for patients and their families. 3,4 According to the International Diabetes Federation (IDF), out of four diabetic people (352 million people), three are of working age (ie, between 20 and 64 years).…”
Section: Introductionmentioning
confidence: 99%
“…Our further analysis of healthcare service utilization found that patients with a history of DM-related complications and an increasing number of comorbidities were associated with greater hospitalization admission rates during the event year. Correspondingly, the increase in direct medical costs was associated with poor glycaemic control, 30 treatment intensification, 31 incidence of DM-related complications 23,32 and all-cause mortality. 22 Annual direct medical costs grew by 95.3% from 2481 US$ during the 2 years preceding the SH event to 4846 US$ during the year immediately preceding the SH.…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing prevalence of diabetes in the world, diabetes and its associated complications, including visual impairment or blindness, caused by DR not only represent a personal disaster, but also become a serious burden to public health (Kähm et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…With the increasing prevalence of diabetes in the world, diabetes and its associated complications, including visual impairment or blindness, caused by DR not only represent a personal disaster, but also become a serious burden to public health (Kähm et al, ). In Canada, diabetes and its associated complications cost $11.7 billion in 2010 and expected to rise to $16 billion by 2020 (Canadian Diabetes Association, ).…”
Section: Introductionmentioning
confidence: 99%